Hypoxia-Induced Autophagy Enhances Cisplatin Resistance in Human Bladder Cancer Cells by Targeting Hypoxia-Inducible Factor-1α - Xiawa Mao; Nanzhang; Jiaquao Xiao; Huifeng Wu; Kefeng Ding (Journal of Immunology Research)
Purpose. To investigate the effect of hypoxia on chemoresistance and the underlying mechanism in bladder cancer cells. Methods. BIU-87 bladder cancer cell line was treated with cisplatin under hypoxic and normoxic conditions and tested using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay, flow cytometry, and Western blotting. All the data were expressed as mean±standard error from three independent experiments and analyzed by multiple t-tests. Results. Apoptosis of bladder cancer cells caused by cisplatin was attenuated in hypoxic conditions. Hypoxia enhanced autophagy caused by cisplatin. The autophagy inhibitor and HIF-1α inhibitor can reverse the chemoresistance in hypoxic condition. Apoptosis and autophagy of bladder cancer cells were downregulated by HIF-1α inhibitor YC-1. Hypoxia-induced autophagy enhanced chemoresistance to cisplatin via the HIF-1 signaling pathway. Conclusion. Resistance to cisplatin in BIU-87 bladder cancer cells under hypoxic conditions can be explained by activation of autophagy, which is regulated by HIF-1α-associated signaling pathways. The hypoxia–autophagy pathway may be a target for improving the efficacy of cisplatin chemotherapy in bladder cancer.